The First Spermatological Examination of New Commercial Fish Species of the Mediterranean: Randall’s Threadfin Bream, Nemipterus randalli Russell, 1986 - Şükrü GÜNGÖR; FEYZA NUR MART; MUHAMMED ENES İNANÇ; DENİZ İNNAL (Cluj Veterinary Journal)
Determining spermatological characteristics in fish is critical for understanding species' reproductive biology, protecting fish stocks, increasing reproductive success, and ensuring fish farming efficiency. While reproductive biology research on native fish species of Mediterranean is restricted, there is no information on the spermatological characteristics of invasive Mediterranean species. Samples were collected from trawl surveys conducted in the Gulf of Antalya (Mediterranean-Turkey) between March and April 2024. The fish samples were promptly transported to the laboratory at the Department of Biology, Burdur Mehmet Akif Ersoy University. The individuals' sex determination, lengths, and weights were recorded. 17 (65.38%) males, 9 (34.62%) females were determined. Male specimens of N. randalli, ranging in size from 19 to 27.2 cm in total length and weighing between 80 and 270.5 g, were analyzed. Nemipterus randalli sperm viability and concentration were evaluated.  Male fish gonads were handled, and testes were dissected in a tube containing 1 ml PBS. Sperm concentration was done with haemocytometric method. The viability of spermatozoa was analysed using a Cytoflex Flow Cytometry device and a Sybr-14/PI double staining method. Spermatozoa concentration of male individuals obtained from the Gulf of Antalya was 160.0±45.63 × 106 spz/ml and the viability rate were 51.71±17.01%. As a result, some spermatological characteristics of Nemipterus randalli, which is recorded as an invasive species and has a serious economic value, were revealed for the first time.